Superficial ocular malignancies treated with strontium-90 brachytherapy: long term outcomes - Laskar, Siddhartha; Gurram, Lavanya; Laskar, Sarbani Ghosh; Chaudhari, Suresh; Khanna, Nehal; Upreti, Rituraj (Journal of Contemporary Brachytherapy, 2015)
Purpose: The incidence of conjunctival malignancies is less than 1%. Though surgical excision remains the mainstay of treatment, the incidence of positive surgical margins and local recurrence rates are high, which is approximately up to 33% in negative margins and 56% in positive margins. Radiotherapy reduces the risk of recurrence in these cases. Brachytherapy using  emitters such as strontium-90 ( 90 Sr) is an ideal treatment technique for these tumors with the advantage of treating only a few millimeters of tissue while sparing the underlying normal eye. We report the long term outcomes in the form of local control and late sequelae of patients with conjunctival malignancies treated with 90 Sr applicator brachytherapy. Material and methods : During 1999-2013, 13 patients with conjunctival tumors, treated using 90 Sr brachytherapy were analyzed. Brachytherapy was either in a post-operative adjuvant or in a recurrent setting. Local control (LC), disease free survival (DFS), overall survival (OS), and late sequelae were evaluated. Results : The median age at presentation was 47 years (range: 11-71 years). Thirteen patients with 15 tumors were treated. The commonest histology was squamous cell carcinoma. The median dose was 44 Gy over 11 fractions. The median follow up of all the patients was 51 months (range: 3-139 months). The median follow up of patients with carcinoma only was 64 months with a LC and DFS of 90.9% at 5 years. None of the patients developed ≥ grade II Radiation Therapy Oncology Group (RTOG) acute toxicities. One patient developed a focal scar and another developed corneal opacification at the limbus. Vision was not impaired in any of the patients. Conclusions : Strontium-90 brachytherapy used in early invasive conjunctival malignancies as an adjunct to surgery in primary and recurrent settings, results in optimal disease control and ocular functional outcomes.